Discovery of electron cyclotron MASER emission from the magnetic Bp star HD 133880 with the Giant Metrewave Radio Telescope. (5th December 2017) - Das, Barnali; Chandra, Poonam; Wade, Gregg A
Abstract: We report the discovery of coherent radio emission from the young, rapidly rotating magnetic Bp star HD 133880 at a frequency of 610 MHz with the Giant Metrewave Radio Telescope (GMRT). This is only the second magnetic star in which coherent radio emission has been detected. In our observations of HD 133880 covering the full rotational cycle of the star (except for a phase window 0.17–0.24), we witness an abrupt order-of-magnitude flux enhancement along with ≈100 per cent right circular polarization. We attribute this phenomenon to coherent electron cyclotron MASER emission. We attribute the lack of left circularly polarized emission to the asymmetric topology of the star's magnetic field. The phase of enhancement, 0.73, differs from the previously reported phase of enhancement, 0.16, (at 610 MHz)by one-half cycle. However, no flux enhancement is found at phase 0.16 in our data, which could be due to an unstable or drifting emission region, or a consequence of the reported changes of the star's rotational period. Either of these factors could have shifted the enhancement to the above-mentioned phase window not sampled by our observations.